Optical Sensors and Actuators for Probing Proximity-Dependent Biotinylation in Living Cells - Chen, Rui; Zhang, Ningxia; Zhou, Yubin; Jing, Ji (Frontiers in Cellular Neuroscience, 2022)
Proximity-dependent biotinylation techniques have been gaining wide applications in the systematic analysis of protein-protein interactions (PPIs) on a proteome-wide scale in living cells. The engineered biotin ligase TurboID is among the most widely adopted given its enhanced biotinylation efficiency, but it faces the background biotinylation complication that might confound proteomic data interpretation. To address this issue, we report herein a set of split TurboID variants that can be reversibly assembled by using light (designated ‘OptoID’), which enables optogenetic control of biotinylation-based proximity labeling in living cells. OptoID could be further coupled with an engineered monomeric streptavidin that permits real-time monitoring of biotinylation with high temporal precision. These optical actuators and sensors will likely find broad applications in precise proximity proteomics and rapid detection of biotinylation in living cells.